Implementation of the E-Bupot System in Order to Provide Convenience to Taxpayers in Fulfilling Article 23 Income Tax Obligations at the KPP Bekasi City Intermediate - Hikmah, Nurul (Indonesian Scientific Publication, 2023)
This research aims to examine the implementation of the e-bupot application in order to provide convenience for taxpayers in fulfilling income tax obligations under article 23. This research was conducted at the Bekasi City Intermediate KPP which is located at M Gold Tower UG Floor, 9, 10 Jalan KH Noer Ali RT.7/RW3, Pekayon Jaya, South Bekasi District, Bekasi City, West Java 17148. This research is descriptive qualitative research which aims to provide an objective picture of the actual situation of the object under study. Data was collected using interviews, observation and documentation methods. Informants in this research were determined using purposive techniques, informants in this research were service staff, taxpayers and academics. The research results show that in the aspect of system quality, e Bupot's ability to facilitate PPH 23 reporting, in terms of information quality, e Bupot has complete information regarding taxpayer requirements, and the type of withholding proof has good information, related to user satisfaction assessed from the aspect of minimal obstacles , each informant has different information such as ownership of e-certificates, minimal knowledge of taxpayers, and the most common are technical errors.